ECONOMIC COMPETITION AND COOPERATION IN THE CONTEXT OF SOCIAL CAPITAL - Mayilyan, Firuza; Gharibyan, Grisha; Isahakyan, Razmik (Bulletin of Yerevan University G: Economics, 2019)
The article discusses the issues of economic competition in the context of social capital theory. Particularly, the role of economic competition as an effective resource allocation mechanism, within the framework of a new classical approach has been analyzed. The positive and negative aspects of the competitive mechanism of resource allocation and economic efficiency have been revealed. The article presents the institutional mechanisms of cooperation as an alternative mechanism of economic system coordination and resource allocation. Mechanisms of cooperation have been discussed in the context of social capital.
Keywords: economic competition, evolution, coordination mechanism, partnership, distribution of social capital